(untitled) (Scientific journal of the Fergana State University, 2023)
The equivalence of the somatic phraseological units with the component “Hand - қўл” in German and Uzbek languages are analyzed in the present article. The full, partial and zero types of equivalents of the somatic phraseological units are enlightened by examples.